A truncating TPO mutation (Y55X) in patients with hypothyroidism and total iodide organification defect. (August 2015) - Cangul, Hakan; Darendeliler, Feyza; Saglam, Yaman; Kucukemre, Banu; Kendall, Michaela; Boelaert, Kristien; Barrett, Timothy G.; Maher, Eamonn R.
Absract Purpose: Mutations in the TPO gene have been reported to cause congenital hypothyroidism (CH), and our aim in this study was to determine the genetic basis of congenital hypothyroidism in two affected children coming from a consanguineous family. Methods: Since CH is usually inherited in autosomal recessive manner in consanguineous/multi case-families, we adopted a two-stage strategy of genetic linkage studies and targeted sequencing of the candidate genes. First we investigated the potential genetic linkage of the family to any known CH locus using microsatellite markers and then screened for mutations in linked-gene by Sanger sequencing. Results: The family showed potential linkage to the TPO gene and we detected a non-sense mutation (Y55X) in both cases that had total iodode organification defect (TIOD). The mutation segregated with disease status in the family. Y55X is the only truncating mutation in the exon 2 of the TPO gene reported in the literature and results in the earliest stop codon known in the gene to date. Conclusions: This study confirms the pathogenicity of Y55X mutation and demonstrates that a nonsense mutation in the amino-terminal coding region of the TPO gene could totally abolish the function of the TPO enzyme leading to TIOD. Thus it helps to establish a strong genotype/phenotype correlation associated with this mutation. It also highlights the importance of molecular genetic studies in the definitive diagnosis and accurate classification of CH.